Noise Characteristics in Presence of Four Wave Mixing in Single Mode Fibers - Muhammad, Haider K. (University of Thi-Qar Journal of Science, 2014)
The transmission system in the fiber optics affected by many conventional noises. In case of employing WDM systems which means the addition of further new noises named nonlinear noises. As far As the FWM is the main important phenomena noise ,all sources of noises being analyzed and a new equation has been set for the FWM .Accordingly the total influence on the allowable input power has been determined, then a general form equation connecting between allowable power and Q-factor has been derived. Since FWM depends on the phase-matching a comprehensive equation has been derived depending on the center of the process mixing.